Pengaruh Kualitas Pelayanan, Harga, dan Citra Merek terhadap Kepuasan Pelanggan Jasa Transportasi Online Grab - Steffany Revina Wulandari; Ari Susanti (Target : Jurnal Manajemen Bisnis, 2021)
This study aims to analyze the effect of service quality, price, and brand image on customer satisfaction with the services of the Gra,b online motorcycle taxi application. The sample in this study was 109 users of transportation services from online motorcycle taxis Grab using the purposive sampling method. Furthermore, the data were analyzed using multiple linear regression to determine the relationship between the variables of service quality, price and brand image on customer satisfaction. The results of research data analysis show that the price variable, brand image partially has a positive and significant effect on customer satisfaction for Grab's online transportation services, while service quality partially has no significant effect on customer satisfaction for Grab's online transportation services.